Performance Characteristics of AOAC Method 2005.06 for the Determination of Paralytic Shellfish Toxins in Manila Clams, European Otter Clams, Grooved Carpet Shell Clams, Surf Clams, and Processed King Scallops. (27th November 2019) - O'Neill, Alison; Turner, Andrew D
Abstract: An approach was developed for the verification of method performance of the AOAC 2005.06 LC-fluorescence detector (FLD) method for determination of paralytic shellfish poisoning (PSP) toxins in bivalve shellfish. This was developed following advice published by the Analytical Laboratory Accreditation Criteria Committee and applied to shellfish species that had not been previously subjected to a full single-laboratory validation scheme. The refined approach was developed following the need to assess performance in a number of shellfish species infrequently monitored through the UK statutory monitoring program, while reducing the impact and cost of the studies, most notably in terms of the use of valuable reference standards. The species assessed were manila clams (Ruditapes philippinarum), European otter clams (Lutraria lutraria), grooved carpet shell clams (R. decussatus), surf clams (Spisula solida), and king scallops ( Pecten maximus ) presented as adductor only or adductor plus roe. The method was assessed for sensitivity in terms of LOD and LOQ, toxin recovery, and method precision in each species. It incorporated the PSP toxins deemed toxic and/or prevalent in UK samples and commercially available as certified reference standards. The toxins studied included GTX1-5, dcSTX, STX, C1&2, and NEO. The toxins dcGTX2&3 were included for surf clams due to the prevalence of these toxins in this species as a result of toxin decarbamoylation. Method performance targets were met for each of the characteristics investigated. Consequently, the method was deemed fit for purpose for the screening and quantification of these clam and scallop species for PSP toxins by AOAC Method 2005.06 LC-FLD.